Communication Strategy to Make MAFI Fest Become a Sustainable Local Film Festival - Puspita, Dinar Chandra; Suharto, Bambang (JURNAL LENSA MUTIARA KOMUNIKASI, 2023)
In the last two decades, the Indonesian film ecosystem has been enlivened by the presence of local film festivals in various cities. The presence of film festivals is often seen as a space to channel interests, express creativity, build networks, and exchange knowledge and experiences. Local film festivals are generally initiated by student associations, film enthusiasts' communities, or government programs. Festival organizers also face various environmental challenges that are unstable in order to maintain their existence. It is not uncommon to find film festivals that have only been successfully held once or a few times, then postponed or discontinued for various reasons. Malang Film Festival (MAFI Fest) is the oldest local film festival initiated by a campus institution and has been able to survive from 2004 until now. This research aims to analyze the communication strategies used by the organizers to establish MAFI Fest as a sustainable local film festival, providing a space of appreciation for filmmakers to showcase their work. The research adopts a qualitative-descriptive approach, and data collection is conducted through interviews, observations, and documentation. The results of the research indicate that MAFI Fest implements repetitive, informative, and educative communication strategies through the media they use. The sustainability of the film festival is inseparable from the shrewdness of the organizers in innovating, support from stakeholders, their ability to obtain funding, and the commitment and activeness of its members. This research contributes to adding insight to academics and practitioners regarding the efforts that can be undertaken to maintain the sustainability of a local film festival in the long run.